2017
DOI: 10.1016/j.jdiacomp.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

H. pylori seroprevalence and risk of diabetes: An ancillary case–control study nested in the diabetes prevention program

Abstract: OBJECTIVE To determine the association between H. pylori infection and risk of incident diabetes in adults at high risk for diabetes who participated in the Diabetes Prevention Program (DPP) study. METHODS In a nested case-control study conducted among 421 adults with newly diagnosed diabetes and 421 matched controls, we examined the association between serological status of H. pylori at baseline and risk of incident diabetes over a mean follow-up period of 2.6 years. Using data from the baseline visit of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
12
0
3
Order By: Relevance
“…Several studies have suggested an association between H pylori , a common infection throughout the world, and glycemic control, insulin resistance, and T2D 17‐20 . On the other hand, some studies concluded that there was no such relationship 21 . Similarly, previous studies have suggested that H pylori infection may cause vitamin‐B 12 deficiency, independent of its interaction with diabetes, but through mechanisms similar to its effect on the parietal cells in the stomach 13,16,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested an association between H pylori , a common infection throughout the world, and glycemic control, insulin resistance, and T2D 17‐20 . On the other hand, some studies concluded that there was no such relationship 21 . Similarly, previous studies have suggested that H pylori infection may cause vitamin‐B 12 deficiency, independent of its interaction with diabetes, but through mechanisms similar to its effect on the parietal cells in the stomach 13,16,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…In a population‐based prospective study performed in China with a 10‐year follow‐up, H. pylori seropositivity was associated with a lower risk of DM (RR: 0.78; 95% CI: 0.63, 0.97; P = 0.02), even after multivariate adjustment for all known risk factors. Conversely, an ancillary case‐control trial within the Diabetes Prevention Program Study found no association between exposure to H. pylori and incident DM (OR: 1.04; 95% CI: 0.77,−1.40) or insulin sensitivity, even after adjusting for matching factors . However, in a case‐control study (174 type 2 DM patients, 185 controls) performed in Iran, Mortazavi et al detected H. pylori CagA positivity in 42.82% of the patients with DM and 22.16% of the control group.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Conversely, an ancillary case-control trial within the Diabetes Prevention Program Study found no association between exposure to H. pylori and incident DM (OR: 1.04; 95% CI: 0.77,−1.40) or insulin sensitivity, even after adjusting for matching factors. 46 suggested that this might be due to the effect of oxidative stress and DNA damage promoted by H. pylori. 48 It has been suggested that H. pylori infection might play a role in the development of hepatic encephalopathy (HE) through systemic inflammation and increased ammonia levels.…”
Section: Iab E Te S Mellitusmentioning
confidence: 99%
“…In addition, successful eradication of H. pylori significantly improves disturbances in these metabolic parameters[ 60 - 63 ]. However, some reports contradict an association between H. pylori and these metabolic risk factors[ 64 - 68 ]. Therefore, we are not able to reach a definitive conclusion, and the effect of H. pylori on metabolic factors may depend on the subjects examined, due to differences in factors such as country of residence, dietary habits, culture, and fitness habits.…”
Section: H Pylori and Nafldmentioning
confidence: 99%